Electrodeposited Lamellar Photoconductor Nanohybrids Driven by Peptide Self‐Assembly. Issue 3 (9th January 2015) - Manna, Manoj K.; Pandey, Sushil K.; Maity, Indrajit; Mukherjee, Shaibal; Das, Apurba K.
Abstract Aromatic organic molecules serve as optoelectronic materials owing to their intrinsic optical and electronic properties. Herein, self‐assembled lamellar nanostructures as photoconductor hybrids, which are obtained from naphthalene‐2‐methoxycarbonyl (Nmoc)‐capped peptide amphiphiles, are described. Hybrid nanostructures are constructed in a controlled manner by an electrochemical deposition technique in combination with the inorganic Zn(OH)2 phase. Inorganic Zn(OH)2 layers turn into semiconductor ZnO layers upon annealing at 150 °C and lamellar nanostructures are formed in a periodic manner. Synergistic effects of hydrogen bonding and π–π stacking interactions of aromatic peptide amphiphiles are the driving force for the formation of self‐assembled lamellar nanostructures. Morphological, structural, and optical studies of such lamellar hybrid nanostructures are reported. Photoconduction of these hybrid nanostructures is also examined in detail.